If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+3-3x=3x-9
We move all terms to the left:
7x+3-3x-(3x-9)=0
We add all the numbers together, and all the variables
4x-(3x-9)+3=0
We get rid of parentheses
4x-3x+9+3=0
We add all the numbers together, and all the variables
x+12=0
We move all terms containing x to the left, all other terms to the right
x=-12
| 25x^2+16x+32=0 | | 4(3x+2)=3x-38 | | 4(y+20)=100 | | 8x-7=6+2(10x-3 | | 2a-5=8a-1 | | 10y+3-3y=28+2y | | 2(7x+5=3(2x+7)+4(2x-1) | | 4x+3=x-21 | | y-12/3=7 | | 10x-x=449 | | X=4x100 | | 30+y/2=55 | | (5u+5)/6+(5u+10)/9+2=7 | | 7q+5/3=4q-30/6 | | -10=4b | | 15+2y=25 | | 2x-3/2x+1=3x+1/3x-1 | | y/3+21=10 | | 18=3⋅x | | P=8x+3 | | x/5+25=15 | | x/2=31/2 | | 2x+5=-7+40 | | 5x+2=3X812 | | 8x-10x+40=0 | | g/2.9=10 | | 4x+4-4x-8=-15-10 | | -4k^2+64k+36=0 | | 8x=10x-40 | | 5x-2(3x±2)=1-2(4x+3) | | 6+x=−8 | | 41-4e=105 |